2007
DOI: 10.1186/1471-2407-7-15
|View full text |Cite
|
Sign up to set email alerts
|

P-LAP/IRAP-induced cell proliferation and glucose uptake in endometrial carcinoma cells via insulin receptor signaling

Abstract: Background: Hyperglycemia or hyperinsulinemia contributes to poorer endometrial cancer survival. It was shown that P-LAP/IRAP translocates to the plasma membrane in response to insulin stimulation. Recently, we demonstrated that P-LAP/IRAP is associated with a poor prognosis in endometrial adenocarcinoma patients. The aim of this study was to examine whether the malignant potential of endometrial cancer enhanced by P-LAP/IRAP is due to increased glucose uptake via the P-LAP/IRAP-mediated activation of insulin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 21 publications
0
8
1
Order By: Relevance
“…In contrast to a basal expression of GLUT4 detected in non-tumorigenic human and rat ovary (Shibata et al, 2007), rat liver (Abel et al, 2001), and rat kidney (supplementary material), Western blotting (Fig. 3) and kinetic analysis (data not shown) revealed that GLUT4 was expressed at negligible levels in both AS-30D hepatocarcinoma and HeLa cells.…”
Section: Low Glut4 Expression In As-30d and Hela Carcinomascontrasting
confidence: 80%
“…In contrast to a basal expression of GLUT4 detected in non-tumorigenic human and rat ovary (Shibata et al, 2007), rat liver (Abel et al, 2001), and rat kidney (supplementary material), Western blotting (Fig. 3) and kinetic analysis (data not shown) revealed that GLUT4 was expressed at negligible levels in both AS-30D hepatocarcinoma and HeLa cells.…”
Section: Low Glut4 Expression In As-30d and Hela Carcinomascontrasting
confidence: 80%
“…Interestingly, the angiotensin-converting enzyme gene, which is also a key component in the renin-angiotensin system, was widely reported to be associated with psoriasis (Weger et al, 2007;Veletza et al, 2008;Lamba et al, 2011) and lends further support to involvement of the renin-angiotensin system in the development of psoriasis. Moreover, LNPEP has also been implicated in diabetes, as it affects glucose uptake via the interaction of insulin receptor signaling with the insulinresponsive glucose transporter GLUT4 (Shibata et al, 2007). It was reported that genetic variants in LNPEP were associated with biological effects on vasopressin clearance and serum sodium regulation (Nakada et al, 2011), which are generally accepted as key biological factors in hypertension, diabetes, and other metabolic phenotypes (Enhorning et al, 2009;Patel and Mehta, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Glucose transporter (GLUT) 1, 4, and 8 expression is upregulated in endometrial cancer cells, and may be linked to tumor progression and differentiation (Goldman et al 2006, Shibata et al 2007. Previous, smaller, prospective (Furberg & Thune 2003), and case-control (Levran et al 1984, Rutanen et al 1993 studies have also observed increased risks associated with high glucose levels.…”
Section: Discussionmentioning
confidence: 99%